Optimization of SVM Classifier by k-NN for the Smart Diagnosis of the Short-Circuit and Impedance Faults in a PV Generator, Dec 2014, ISSN/ISBN 1974-9821 / 1974-983X - Rezgui Wail; Mouss kinza Nadia; Mouss Med Djamel (IREMOS International Review on Modelling and Simulations, 2014)
This paper deals with a new algorithm allowing short-circuit and impedance faults smart diagnosis of PV generators. It is based on the use of the SVM technique for the classification of observations not located in its margin, otherwise the proposed algorithm is used a k-NN method. A PV generator database containing observations distributed over classes is used for testing the new algorithm performance, which shows therefore its contribution and its effectiveness in the diagnosis area.